Insights into a type III cohesin–dockerin recognition interface from the cellulose‐degrading bacterium Ruminococcus flavefaciens1. Issue 3 (30th January 2015) - Weinstein, Jonathan Y.; Slutzki, Michal; Karpol, Alon; Barak, Yoav; Gul, Ozgur; Lamed, Raphael; Bayer, Edward A.; Fried, Daniel B.; Fleminger, Gideon; Jungbauer, Alois
<x xml:space="preserve">Abstract</x> Cellulosomes are large multicomponent cellulose‐degrading assemblies found on the surfaces of cellulolytic microorganisms. Often containing hundreds of components, the self‐assembly of cellulosomes is mediated by the ultra‐high‐affinity cohesin–dockerin interaction, which allows them to adopt the complex architectures necessary for degrading recalcitrant cellulose. Better understanding of how the cellulosome assembles and functions and what kinds of structures it adopts will further effort to develop industrial applications of cellulosome components, including their use in bioenergy production. Ruminococcus flavefaciens is a well‐studied anaerobic cellulolytic bacteria found in the intestinal tracts of ruminants and other herbivores. Key to cellulosomal self‐assembly in this bacterium is the dockerin ScaADoc, found on the non‐catalytic structural subunit scaffoldin ScaA, which is responsible for assembling arrays of cellulose‐degrading enzymes. This work expands on previous efforts by conducting a series of binding studies on ScaADoc constructs that contain mutations in their cohesin recognition interface, in order to identify which residues play important roles in binding. Molecular dynamics simulations were employed to gain insight into the structural basis for our findings. A specific residue pair in the first helix of ScaADoc, as well as a glutamate near the C‐terminus, was identified to be essential for cohesin binding. By advancing our understanding of the cohesin binding of ScaADoc, this study serves as a foundation for future work to more fully understand the structural basis of cellulosome assembly in R. flavefaciens. Copyright © 2015 John Wiley & Sons, Ltd.